Internal validity in resistance training research: A systematic review - Makaruk, H.; Starzak, M.; Plaszewski, M; Winchester, J. B. (Journal of Sports Science & Medicine, 2022)
Ensuring internal validity is the key procedure when planning the study design. Numerous systematic reviews have demonstrated that considerations for internal validity do not receive adequate attention in the primary research in sport sciences. Therefore, the purpose of this study was to review methodological procedures in current literature where the effects of resistance training on strength, speed, and endurance performance in athletes were analyzed. A computer-based literature searches of SPORTDiscus, Scopus, Medline, and Web of Science was conducted. The internal validity of individual studies was assessed using the PEDro scale. Peer-reviewed studies were accepted only if they met all the following eligibility criteria: (a) healthy male and female athletes between the ages of 18-65 years; (b) training program based on resistance exercises; (c) training program lasted for at least 4 weeks or 12 training sessions, with at least two sessions per week; (d) the study reported maximum strength, speed, or endurance outcomes; and (e) systematic reviews, cohort studies, case-control studies, cross-sectional studies were excluded. Of the 6,516 articles identified, 133 studies were selected for rating by the PEDro scale. Sixty-eight percent of the included studies used random allocation to groups, but only one reported concealed allocation. Baseline data are presented in almost 69% of the studies. Thirty-eight percent of studies demonstrated adequate follow-up of participants. The plan to follow the intention-to-treat or stating that all participants received training intervention or control conditions as allocated were reported in only 1.5% of studies. The procedure of blinding of assessors was also satisfied in only 1.5% of the studies. The current study highlights the gaps in designing and reporting research in the field of strength and conditioning. Randomization, blinding of assessors, reporting of attrition, and intention-to-treat analysis should be more fully addressed to reduce threats to internal validity in primary research.